Causes of acute, undifferentiated, febrile illness in rural Thailand: Results of a prospective observational study - C. Suttinont (2018)
The adult patients who, between July 2001 and June 2002, presented at any of five hospitals in Thailand with acute febrile illness in the absence of an obvious focus of infection were prospectively investigated. Blood samples were taken from all of the patients and checked for aerobic bacteria and leptospires by culture. In addition, at least two samples of serum were collected at different times (on admission and 2-4 weeks post-discharge) from each patient and tested, in serological tests, for evidence of leptospirosis, rickettsioses, dengue and influenza. The 845 patients investigated, of whom 661 were male, had a median age of 38 years and a median duration of fever, on presentation, of 3.5 days. Most (76.5%) were agricultural workers and most (68.3%) had the cause of their fever identified, as leptospirosis (36.9%>), scrub typhus (19.9%), dengue infection or influenza (10.7%), murine typhus (2.8%), Rickettsia helvetica infection (1.3%), Q fever (1%), or other bacterial infection (1.2%). The serological results indicated that 103 (12.2%) and nine (1%) of the patients may have had double and triple infections, respectively. Leptospirosis and rickettsioses, especially scrub typhus, were thus found to be major causes of acute, undifferentiated fever in Thai agricultural workers. © 2006 The Liverpool School of Tropical Medicine.